Debt, Taxes, and Banks - Keen, Michael (IMF Working Papers; Working Paper, 2012)
Understanding the impact of the asymmetric tax treatment of debt and equity on the capital structures of financial institutions is critical to shaping and assessing responses to the problem of excessive leverage that underlay the 2009 financial crisis - but there is no empirical evidence to draw on. Guided by a simple model of banks? financing decisions in the presence of both regulatory constraints and tax asymmetries, this paper explores the impact of corporate tax bias on bank leverage, the use of hybrid instruments and regulatory capital ratios for a panel of over 14,000 commercial banks in 82 countries over nine years. On average, the sensitivity of banks? debt choices proves very similar to that of non-financial firms, consistent with rough offsetting of two opposing effects suggested by the theory. As the model predicts, somewhat counter-intuitively, the impact of tax on hybrids is generally weak or insignificant. Responsiveness to taxation varies significantly across banks, however: those holding smaller equity buffers, and larger banks, are noticeably less sensitive to tax.